Sistem Pakar Mendiagnosa Penyakit Tropik Infeksi Dengan Menggunakan Metode Certainty Factor (CF) - Ira Tasya Mawaddah; Sulindawaty Sulindawaty (Jurnal Sains dan Teknologi, 2022)
The impact of computer technology has played a major role in changing aspects of human life, especially in the health sector where in the midst of an epidemic that hit a system that is able to reduce the impact of the crowd is needed. One of them is a system for diagnosing disease, and the disease to be studied is a type of infectious disease and a disease that is increasing in the midst of an epidemic, namely infectious tropical diseases or diseases that develop in a tropical climate. The purpose of this study is to build a web-based expert system application that is able to diagnose infectious tropical diseases using the certainty factor (CF) method, and development using the waterfall model. Tests are carried out with blackbox tests and validity tests, on blackbox tests the system runs as expected and on the validity test the system is declared valid to be used. In the user test, the calculation obtained using the CF method is 97.65% certainty level. The research concludes that the system is able to provide a confidence value and can diagnose the type of infectious tropical disease based on the symptoms selected by the user. Because the system still has limitations, it is hoped that the system will be developed using other methods so that it is more useful for users.